Analysis of Machine Learning Methods for COVID-19 Detection Using Serum Raman Spectroscopy. Issue 14 (6th December 2021) - Chen, David
ABSTRACT: One of the most challenging aspects of the emergent coronavirus disease 2019 (COVID-19) pandemic caused by infection of severe acute respiratory syndrome coronavirus 2 has been the need for massive diagnostic tests to detect and track infection rates at the population level. Current tests such as reverse transcription-polymerase chain reaction can be low-throughput and labor intensive. An ultra-fast and accurate mode of detecting COVID-19 infection is crucial for healthcare workers to make informed decisions in fast-paced clinical settings. The high-dimensional, feature-rich components of Raman spectra and validated predictive power for identifying human disease, cancer, as well as bacterial and viral infections pose the potential to train a supervised classification machine learning algorithm on Raman spectra of patient serum samples to detect COVID-19 infection. We developed a novel stacked subsemble classifier model coupled with an iteratively validated and automated feature selection and engineering workflow to predict COVID-19 infection status from Raman spectra of 250 human serum samples, with a 10-fold cross-validated classification accuracy of 98.0% (98.6% precision and 98.5% recall). Furthermore, we benchmarked nine machine learning and artificial neural network models when evaluated using eight standalone performance metrics to assess whether ensemble methods offered any improvement from baseline machine learning models. Using a rank-normalized scores derived from the performance metrics, the stacked subsemble model ranked higher than the Multi-layer Perceptron, which in turn ranked higher than the eight other machine learning models. This study serves as a proof of concept that stacked ensemble machine learning models are a powerful predictive tool for COVID-19 diagnostics.